2013
DOI: 10.1093/occmed/kqt054
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and negative affectivity: a multi-method study

Abstract: NA influenced psychophysical strain in the worker, both directly and indirectly, through perceived conflict with co-workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
3
22
0
1
Order By: Relevance
“…Additionally, Oliver et al (2010) found in a longitudinal study that NA predicts work stressors over time, but work stressors do not predict NA over time. Finally, interpersonal conflict at work has been associated with both negative affective reactions in diary studies (Ilies et al, 2011;Meier et al, 2013) and with psychophysical strain in longitudinal studies (Falco et al, 2013b;Nixon et al, 2011). Overall, although more research is needed in order to examine the relationship between NA, ICW, and pro-inflammatory cytokines, the complete mediation model seems therefore consistent with current theories and evidence.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Additionally, Oliver et al (2010) found in a longitudinal study that NA predicts work stressors over time, but work stressors do not predict NA over time. Finally, interpersonal conflict at work has been associated with both negative affective reactions in diary studies (Ilies et al, 2011;Meier et al, 2013) and with psychophysical strain in longitudinal studies (Falco et al, 2013b;Nixon et al, 2011). Overall, although more research is needed in order to examine the relationship between NA, ICW, and pro-inflammatory cytokines, the complete mediation model seems therefore consistent with current theories and evidence.…”
Section: Discussionsupporting
confidence: 56%
“…Negative affectivity was determined using the Italian version of the Strain-Free Negative Affectivity Scale (Fortunato et al, 1999; see also Falco et al, 2013b), a 9-item scale with responses ranging from 1 (strongly disagree) to 6 (strongly agree). Cronbach's alpha in our study was .74.…”
Section: Negative Affectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 The evaluation of workers' performance was supplied by the supervisor, in the context of the evaluation of annual performances. In particular, the supervisor expressed a judgment for each worker, using a 10-point scale.…”
Section: Participants and Proceduresmentioning
confidence: 99%